Coherent Organizational Practices and Workplace Empowerment: Empirical Evidence from Practicing Organization - Mokshagundam, S. Sriranjani; Gopal, Sagar; MM, Bagali (International Journal of Psychosocial Rehabilitation, 2025)
During turbulent days, organizations are increasingly seen to innovate ways to manage business. One of these innovations is in the area of developing and managing human resources. Experience has shown that developing human resources often results in achieving a sustained organizational growth. Various strategies are being adopted by business organizations in this regard. One also sees a paradigm shift from an approach understood as ‘welfare approach’ to that of an approach commonly known as the ‘empowerment approach’. This approach of employee empowerment has seen interesting outcomes and hence has been accepted almost all across the world. This paper is an empirical study of Indian industry. It highlights some unique strategies adopted for managing human resources in this industry. The efforts have paid large dividends to the company. The workforce is committed as well as efficient. The business organization has succeeded and has been able to achieve global standards. This paper makes an attempt to advocate the cause of employee empowerment and calls upon practitioners to shift their practices from that of welfare orientation to empowerment. The paper also makes an attempt to demystify the concept of employee empowerment.